Energy - Dodd, Emily (London DK Publishing, 2018)
A perfect introduction to energy, this fact-packed book teaches children all about energy and how it works. From electricity and light, to heat and sound, learn how different types of energy are part of everything we do. Discover how a rainbow is made, what renewable energy is, and meet an energy expert. Filled with exciting information, simple science, and colourful illustrations, DKfindout! Energy brings energy to life. With key topics, such as conductors and insulators and fossil fuels, broken down into bite-sized chunks, the information is easily digestible and great for beginners
Science
1 2
Keywords: Force and energy -- Juvenile literature; Power resources -- Juvenile literature